2016
DOI: 10.1098/rsob.160186
|View full text |Cite
|
Sign up to set email alerts
|

piRNA-associated proteins and retrotransposons are differentially expressed in murine testis and ovary of aryl hydrocarbon receptor deficient mice

Abstract: Previous studies suggested that the aryl hydrocarbon receptor (AhR) contributes to mice reproduction and fertility. However, the mechanisms involved remain mostly unknown. Retrotransposon silencing by Piwi-interacting RNAs (piRNAs) is essential for germ cell maturation and, remarkably, AhR has been identified as a regulator of murine B1-SINE retrotransposons. Here, using littermate AhR+/+ and AhR−/− mice, we report that AhR regulates the general course of spermatogenesis and oogenesis by a mechanism likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…One relevant question that remains to be investigated is to what extent the effects reported here depend on the expansion of liver stem-like cells, on the absence of AhR in those cells or on both phenomena. The first possibility is supported by recent observations from our laboratory showing that AhR deficiency also improves lung regeneration after naphthalene-induced damage through an increase in the pool of basal and Clara stem-like cells (Hernández-Morales, unpublished observations), and that AhR-null testes have increased levels of early progenitor cells 25 . The second would imply that AhR deprivation triggers cell autonomous effects leading to undifferentiation and stemness.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…One relevant question that remains to be investigated is to what extent the effects reported here depend on the expansion of liver stem-like cells, on the absence of AhR in those cells or on both phenomena. The first possibility is supported by recent observations from our laboratory showing that AhR deficiency also improves lung regeneration after naphthalene-induced damage through an increase in the pool of basal and Clara stem-like cells (Hernández-Morales, unpublished observations), and that AhR-null testes have increased levels of early progenitor cells 25 . The second would imply that AhR deprivation triggers cell autonomous effects leading to undifferentiation and stemness.…”
Section: Discussionmentioning
confidence: 80%
“…Reverse transcription was done using random priming and the iScript Reverse Transcription Super Mix (Bio-Rad). Real-time PCR (qPCR) was performed using SYBR® Select Master Mix (Life Technologies) in a Step One Thermal Cycler (Applied Biosystems) as indicated 25 , 33 . Gapdh was used to normalize target gene expression (ΔCt) and 2 −ΔΔCt to calculate changes in mRNA levels with respect to untreated conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have first found that zygotes from AhR -/- mice have basal overexpression of well-known pluripotency factors Oct4, Nanog and Sox2 , in agreement with our previous studies showing that AhR-null mice have an increased ability to regenerate lung (Morales-Hernandez et al, 2017) and liver (Moreno-Marin et al, 2017) and a higher potential to sustain undifferentiation of human embryionic carcinoma cells (Morales-Hernandez et al, 2016). The apparent global role of AhR in controlling differentiation was also reported by its ability to regulate ovarian follicular development through piRNA-associated proteins, piRNAs and retrotransposons (Rico-Leo et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, FICZ (10 nM) regulated the transcription of Alu retrotransposons located in the upstream promoter regions of the pluripotency genes NANOG and OCT4 (Morales-Hern andez et al 2016). When administered by injection into mouse testes, 4 lg FICZ kg À1 also repressed the germ-line specific genes MVH, Mili, and Miwi, effects mediated by the AHR and proposed to control the expression of small non-coding TEs involved in the maturation of germ cells (Rico-Leo et al 2016).…”
Section: Ficz Stimulates Intrachromosomal Exchange and Retrotransposimentioning
confidence: 99%